2018
DOI: 10.1136/bmjsem-2018-000470
|View full text |Cite
|
Sign up to set email alerts
|

Accumulated or continuous exercise for glycaemic regulation and control: a systematic review with meta-analysis

Abstract: ObjectiveTo compare the effectiveness of accumulating exercise in multiple bouts of at least 10 min throughout a day with exercise completed in a single bout (continuous or interval), or no exercise, on glycaemic control and regulation in inactive people without diagnosed glycaemic dysfunction.DesignSystematic review and meta-analysis.Data sourcesSeven electronic databases were searched: CINAHL (EBSCO), Cochrane Library, EMBASE (Ovid), MEDLINE 1948-(Ovid), SCOPUS (Elsevier), SPORTDiscus (EBSCO) and Web of Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…It is important to highlight that mean baseline levels of fasting glucose, insulin and HbA1c were mostly within normal ranges in available meta-analyses (78,134,135), which may partly explain the small magnitude of reported changes following SB interventions. In fact, these small changes are comparable to the findings that have been observed with continuous exercise in people without glycemic dysfunction (230).…”
Section: Clinical Significancesupporting
confidence: 86%
“…It is important to highlight that mean baseline levels of fasting glucose, insulin and HbA1c were mostly within normal ranges in available meta-analyses (78,134,135), which may partly explain the small magnitude of reported changes following SB interventions. In fact, these small changes are comparable to the findings that have been observed with continuous exercise in people without glycemic dysfunction (230).…”
Section: Clinical Significancesupporting
confidence: 86%
“…On top of that, multiple short periods of PA (< 10 min) have been shown to be more attractive for the sedentary populations than longer continuous bouts, while they still significantly improve physical fitness [119,120]. Accumulated and continuous exercises have shown to elicit similar effects on physical fitness, cardiovascular and cardiometabolic parameters in inactive and sedentary populations [121,122].…”
Section: Discussionmentioning
confidence: 99%
“… 23 24 Murphy and colleagues 23 reviewed 16 studies and reported similar health benefits in blood pressure, weight loss, and lipid profiles of dividing the same amount of exercise into frequent shorter or fewer longer sessions. Furthermore, Shambrook and colleagues 24 performed a systematic review of 16 studies in sedentary healthy persons and concluded that the glycemic response to accumulated exercise or single-bout exercise was the same.…”
Section: Discussionmentioning
confidence: 99%